Anti-social: An ethnographic account social media within a technically restrictive public sector agency - O’Connor, Ben (Journal of Interdisciplinary Studies in Education, 2019)
This article provides an ethnographic account of an action-research practitioner’sexperience in social media usage within a public-sector agency that discouragesand actively restricts social media usage on its ICT networks, and invokes policyagainst employee social media use. The agency is unique in the commercial,scientific and advisory services it provides, meaning that the sensitive nature ofthe work precludes the agency from being clearly identified – also a factor in itsdecision to restrict social media access. Nonetheless, events in similarly sizedentities, such as the Royal Australian Navy, provide context for this study, anddevelopments in other public sector agencies that offer similar services areprovided to offer a frame of reference. Looking at the three main ways thatemployees are using social media at work, this examination discusses theimplications for the future of collaborative work practices, and engagement withbroader professional interests.